PEMANFAATAN BARANG BEKAS SEBAGAI MEDIA PEMBELAJARAN IPA DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII SMP SWASTA SATRYA MANDIRI BANDAR TONGAH - Rajagukguk, Salome; Dianti Siboro, Thiur; Epiyani, Putri (Jurnal Metabio, 2024)
This research aims to determine the effect of using used goods as a science learning medium on respiratory system material in developing the creative thinking abilities of class VIII students at Satrya Mandiri Private Middle School. The method used is a quantitative approach, experimental method. Data collection techniques in this research are pretest and posttest. The data analysis technique carried out in this research consists of 2 stages, namely prerequisite testing and hypothesis testing. using the SPSS 2.3 for Windows program. From the results of the linearity test, it is known that the two variables (media use and creative thinking ability) have a significant linear relationship. From the results of the normality and homogeneity tests, it was obtained that the control and experimental class data were normally distributed and had the same variance (homogeneous). From the results of hypothesis testing with the t test, it is obtained that t count (2.824) > t table (1.701), then Ho is rejected and Ha is accepted, meaning that there is an influence on the use of used goods as knowledge. learning media in developing creative thinking abilities of class VIII students at Satrya Mandiri Private Middle School. Based on the F test that has been carried out, the calculated F is 23.603 so the df is 28 and the real level is 5% so the F table is 4.210. F count > F table then Ha is accepted. This means that there is a significant influence if learning is carried out using used media in class VIII on the human respiratory system material at the Satrya Mandiri Private Middle School in Bandar Tongah. It was concluded that there was an influence of using used goods as a science learning medium in developing the creative thinking abilities of class VIII students at the Satrya Mandiri Private Middle School in Bandar Tongah.